Evaluation of Monocyte Chemoattractant Protein-1 levels as diagnostic biomarker of Diabetic Retinopathy. - Ahmed , Shabir; Anjum, Nargis; Muhammad Irfan; Ramzan, Adil; Wasee, Nosheen; Zia, Nuvair (International Journal of Endorsing Health Science Research, 2022)
Background: Monocyte Chemoattractant Protein-1 (MCP-1) is an inflammatory bio-peptide which release into body circulation in specific response to retinal inflammation. The objective of the current study was to find the levels of monocyte chemoattractant protein-1 in diabetic patients with and without diabetic retinopathy and to compare the functional role of MCP-1 as a better diagnostic biomarker in the early phase of diabetic retinopathy with conventional methods. Methodology: This case-control study was conducted at the Physiology Department of Basic Medical Science Institute (BMSI), Jinnah Postgraduate Medical Center (JPMC)-Karachi, from April 2019 to October 2020. Total 100 participants between 40-65 years of age were separated into four groups: Group A (n=25) diabetic-patients with diabetes duration 5-7 years with no retinopathy; Group B (n=25) diabetic patient’s diabetes duration 8-10 years with mild retinopathy, Group C (n=25) diabetic patient’s diabetes duration 10-15 years with moderate retinopathy while Group D (n=25) healthy normal individuals. All study participants were gone through a detailed history and blood sugar levels, visual acuity, slit-lamp examination, and serum MCP-1 were estimated. Results: The present study reported significantly elevated levels of MCP-1 among group-A (without retinopathy), group B (mild diabetic retinopathy), and Group- C (moderate retinopathy), while Group-D (healthy controls) had the least level of MCP-1 (p-value=0.001) that indicate the early phase of retinal inflammation. Current study has shown strong association between MCP-1 with duration of disease (r=0.885; p < 0.01), and HbA1c (r =0.71; p <0.01) in all study participants. While statistically significant and positive association and correlation were reported between MCP-1 with blood sugar parameters (fasting and random) (r = 0.876; p< 0.01) in all study participants. Conclusion: Elevated levels of MCP-1 with the progression of early retinal inflammation diabetic retinopathy had been reported in the current study. These findings conceivably propose that MCP-1 could be an early diagnostic marker for an additional diagnostic tool for early detection of diabetic retinopathy compared with all conventional clinical findings.